Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

Microbial network stability is linked to soil multifunctionality and functional trade-offs under long-term fertilization in a dryland agroecosystem - Fangfang Li; Xihe Wang; Yaping Huang; Xin Li; Lei Wu; Jinyu Yang; Wanli Xu; Wenju Zhang (Agriculture, Ecosystems & Environment, 2027)

METTL3 suppresses pyroptosis in obstructive sleep apnea-associated hypertension via YTHDF2-mediated SOX4 mRNA degradation - Wenjun Zhu; Yanyan Hou; Can Yang; Yaping Tian; Linna Cao; Wenjun Li; Liang Xie; Lirong He (Journal of Physiology and Biochemistry, 2026)

Augmented innate and humoral immune responses enhance early and durable rabies protection by a CD40L-overexpressing rabies vaccine - Xiao Xing; Yufang Wang; Zhimin Xiong; Die Liu; Yong Wang; Yang Hu; Yaping Liu; Yingying Li (Veterinary Microbiology, 2026)

Revealing spatiotemporal patterns of metro tidal ridership and their relationships with TOD features: A dual-sequence clustering and explainable machine learning approach - Rui An; Zhaomin Tong; Xiping Yang; Yaping Wang; Ying Jing; Yaolin Liu; Lin Luo; Jiayu Liu (Travel Behaviour and Society, 2026)

Optimizing Holstein bovine oocyte development: Evidence-Based donor selection for OPU-IVP - Heqiang Li; Baobao Zhao; Jingya Wang; Xuexiao Song; Jieyu Wang; Yang Li; Zihan Xu; Zheng Wang; Yaochang Wei; Zhuangsheng Wang; Yaping Jin; Yongsheng Wang (Theriogenology, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

Chemical constituents from the aerial parts of Rauvolfia yunnanensis Tsiang and their chemotaxonomic significance - Wanqi Yang; Xiaoyan Cui; Renfeng Ye; Min Jiang; Shijing Tang; Wenjing Dong; Guiguang Cheng; Yaping Liu (Biochemical Systematics and Ecology, 2026)

Pore-scale heat transfer analysis in grain piles via X-ray CT and LBM - Xiaoliang Wang; Ying Zhou; Yaping Shi; Yanbo Hui; Ju Gao; Yihui Wang; Fan Yang (Journal of Food Engineering, 2026)

Combined CO₂ and topographic uplift forcing on vegetation and climate change in the North China Plain since ∼6.5 Ma - Wei Liu; Likang Wang; Zhenjing Yang; Dianbao Chen; Dexuan Chen; Yaping Li; Xiaozhong Huang; Yunfa Miao; Baotian Pan (Global and Planetary Change, 2026)

The exosomal bta-miR-1246/ATOH8 signaling axis: A key Regulator of intramuscular adipocytes development and beef marbling - Yaping Song; Dongmei Yang; Chao Jiang; Xiaoyu Song; Ruopu Jiao; Hongfang Gong; Yilun Ma; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Guijie Zhang; Yun Ma; Linsen Zan; et al. (Food Bioscience, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Metabolic engineering of Dunaliella salina enhances astaxanthin production: combined effects of heterologous enzyme co-expression and dual-stress optimization - Hao Zhang; Yifan Kong; Yaping Shao; Ziqi Zhang; Celong Zhao; Fuhao Xu; Fenglin Yang; Fengjie Sun; Yulin Cui; Yuyong Wu; Chunxiao Meng; Zhengquan Gao (World Journal of Microbiology and Biotechnology, 2026)

Rhizosphere inoculation with Streptomyces pactum is associated with sugar-related fruit quality and rhizosphere variation in goji berry (Lycium barbarum L.) - Yaping Ma; Jie Cao; Ping Yang; Yusupu Wayiti; Shuo Han; Kelong Wang; Alimire Ailimujiang; Yue Zhang (Plant and Soil, 2026)

Seismic rock-physics inversion for petrophysical parameters in deep coalbed methane reservoirs with complex pore structures - Qiang Guo; Yang Chen; Yaping Huang; Jing Ba (Journal of Applied Geophysics, 2026)

A subset of cell cycle regulators co-expresses with cholesterol pathway and innate immune signaling during early GCRV infection in CIK cells - Waqar Younas; Lei Zhang; Mijuan Shi; Hong Yang; Yingyin Cheng; Wanting Zhang; Yaping Wang; Xiao-Qin Xia (Fish & Shellfish Immunology, 2026)

Sub-chronic copper exposure alters growth performance, intestinal histopathology, and intestinal microbiota in adult zebrafish (Danio rerio) - Yaping Wang; Yaqian Fu; Xuyang Zhai; Chang Dong; Mengdie Yang; Ziyi Huang; Fei Liu (Ecotoxicology, 2026)

A Survey of the Species Origins of Common Fish Cell Lines—With a Particular Focus on the Grass Carp Ovarian Cell Line ( GCO ) - Hong Yang; Mijuan Shi; Yingyin Cheng; Wanting Zhang; Bin Gui; Rong Huang; Yaping Wang; Xiao‐Qin Xia (Journal of Fish Diseases, 2026)
Cell line misidentification or contamination undermines the reliability of research outcomes. In this study, we verified the species origin of commonly used fish cell lines, with a particular focus on the grass carp ovarian cell line (GCO). RNA‐seq data from 146 samples of 11 widely used fish cell lines were collected from public databases (NCBI‐SRA) and were mapped to the reference genomes of eight species. GCO RNA‐seq samples from three Chinese laboratories showed a mapping rate of 21.64% ± 3.61% to the grass carp genome, but 89.81% ± 4.83% to the fathead minnow genome. Further transcriptomic similarity analysis revealed that these GCO RNA‐seq samples clustered more closely with cell lines originating from fathead minnow. Targeted analysis of the COI gene amplification region confirmed that nearly all reads from GCO RNA‐seq samples mapped exclusively to the fathead minnow COI amplicon. Collectively, these results indicate that GCO may have undergone cross‐contamination or species misidentification. This study raises doubts about the true species origin of the GCO cell line and proposes that COI DNA barcoding can be used to discriminate the species origin of fish cell lines.

Enhancing the leaching of copper oxide ores with high contents of calcium-magnesium alkaline bearing gangue by carboxymethyl chitosan - Jinrui Zhou; Wei Guo; Siqi Yang; Xianping Luo; Louyan Shen; Zhiyong Gao; Hongbo Zhao; Yaping Liu (Minerals Engineering, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Bisphenol A exposure disrupts the circadian clock system and impairs glycolipid metabolic function in mice liver - Hao Dong; Wenli Ding; Bonan Xiao; Cuimei Li; Haizhen Jiang; Wanghao Yang; Dan Li; Chao Li; Haisen Zhang; Dengke Gao; Aihua Wang; Yaping Jin; et al. (Food and Chemical Toxicology, 2026)

Hydrogen production via gasification of corn stover photo-fermentation Residue: Catalytic mechanism of alkali metals - Kaixin Wang; Xiaoyu Yan; Yaping Zheng; Jiatao Dang; Sen Yao; Wei Wang; Panbo Yang; Shuheng Zhao; Jianjun Hu (Bioresource Technology, 2026)

A real-world pharmacovigilance study of dacomitinib based on FDA adverse event reporting system (FAERS) database - Yuqin Yang; Yaping Huang; Yifan Wang; Chengjie Ke; Maohua Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Coupling near infrared spectroscopy with machine learning algorithms for simultaneously detecting multiple microplastics in soil - Jia Long; Xi Li; Renjie Yang; Guimei Dong; Yaping Yu; Huiyong Shan (Journal of Soils and Sediments, 2026)

SETD2 Improves Endothelial Function and Angiogenesis in Diabetic Hindlimb Ischemia Via Activating ANGPT2-PI3K/AKT Pathway - Langtao Wang; Qing Wang; Jiaxing Duan; Yu Tan; Yuanyuan Liu; Shuai Hu; Cheng Wang; Chen Yang; Yanzhu Long; Jinxuan Wang; Tao Yu; Tianhu Liu; et al. (Cardiovascular Toxicology, 2026)

Large-scale farming enhances soil health in contrast to smallholder management: Insights from a field survey - Xin LI; Dong WU; Yaping HUANG; Xiao YANG; Gilles COLINET; Caroline DE CLERCK; Wenju ZHANG; Minggang XU; Jeroen MEERSMANS (Pedosphere, 2026)

Tuning CO2 separation of Type I UiO-66 porous liquids by varying the size of porous hosts - Shuangshuang Long; Jingwen Wang; Shuqian Meng; Yaxin Liu; Jing Zhang; Zihao Ren; Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Libing Qian; Wenwu Zhou; et al. (Journal of Environmental Chemical Engineering, 2026)

From syngas to food - high-moisture extrusion of Clostridium autoethanogenum protein into fibrous meat analogues - Tao Ding; Zhougang Chen; Yuchen Zhao; Hao Wang; Xiaofang Liang; Jie Wang; Jie Yang; Yaping Zhu; Shifeng Ma; Min Xue (Food Research International, 2026)

Promoting the lattice oxygen mechanism via electronic modulation: Cobalt doping and heterointerface effects in RuO2@CuO for enhanced acidic oxygen evolution catalysis - Yuhe Zhang; Yuhui Sun; Yuchen Yang; Yaping Tang; Wei Jiang; Xianyu Chu; Chunbo Liu; jihui Lang; Yuanyuan Wu; Feifan Guo (Chemical Engineering Journal, 2026)

Characterization of T5DL·5DS-2RS, a wheat-rye chromosomal translocation with enhanced grain hardness and pre-harvest sprouting resistance - Xin Liu; Huiting Zhang; Zhenglan Cao; Yanhong Lei; Mengyu Han; LiBin Wang; Yilong Dong; Jishan Niu; Yaping Cao; Jiajia Zhao; Jun Zheng; Xueming Yang; et al. (Theoretical and Applied Genetics, 2026)

Ectomycorrhizal and saprotrophic fungi are linked to reduced pathogenic fungi across roots and rhizosphere soils of major afforestation species in northeastern China - Wen Guo; Xiangxia Yang; Yaping Liu; Xiaoding Lin; Le Chang; Yaru Wei; Mingming Xia; Minghao Lv; Kazuo Isobe (Soil Ecology Letters, 2026)

Design, synthesis, and biological evaluation of glycyrrhetinic acid–cinnamamide derivatives as HMGB1/TLR4 pathway inhibitors for sepsis-induced liver injury - Jiao Wang; Tian Guo; Zhe Zheng; Yaping Zhang; Zhian Zha; Xiaohan Zhang; Jie Song; Dongyi Wei; Jianbin Yang (Molecular Diversity, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

Early nut exploitation and its potential for the adaptation of hunter-gatherers to climate change during the LGM in southern China - Qingjiang Yang; Keliang Zhao; Lingxia Zhao; Xinying Zhou; Lili Lu; Yaping Zhang; Lizhao Zhang; Jian Wang; Xinyi Lu; Xiaoqiang Li (Science China Earth Sciences, 2026)

(P)ppGpp synthase Rsh promotes persister cells formation by regulating sulfur metabolism mediated by sulfate reductase CysI in Brucella abortus - Xiaofang Liu; Chenyang Cui; Pingping Wang; Hui Wang; Yunyi Zhai; Yuanhao Yang; Jialu Chen; Wei Liu; Zheng Dong; Dong Zhou; Yaping Jin; Aihua Wang (Veterinary Microbiology, 2026)

Analysis of WNT5A as a key regulator of intramuscular fat deposition in muscle-adipocyte co-cultures - Hongfang Gong; Yaping Song; Dongmei Yang; Chao Jiang; Ruopu Jiao; Yilun Ma; Sayed Haidar Abbas Raza; Jiupan Zhang; Dawei Wei (Tissue and Cell, 2026)

HSF-1 Regulates Autophagy to Govern Motor Function and Facilitate Toxic Protein Clearance in a C. elegans Model of Amyotrophic Lateral Sclerosis - Hui Xu; Yaping Shao; Jun Zhang; Yang Ni; Guowang Xu; Cong Liu; Yi Liang; Weidong Le (Neuroscience Bulletin, 2026)

Long-term fertilization-induced increases in glomalin-related soil protein depend on phosphorus input and aggregate stability across climatic zones - Hongbo Yang; Guanmo Li; Dong Wu; Qiong Xiao; Xin Li; Yaping Huang; Jeroen Meersmans; Gilles Colinet; Minggang Xu; Wenju Zhang (Soil and Tillage Research, 2026)

Selective CO2 photoreduction to acetate enabled by charge-enriched interface sites confined in metal nanoclusters - Juncheng Zhu; Yang Wu; Jun Hu; Zijia Lin; Zexun Hu; Mingyu Wu; Runhua Chen; Kai Zheng; Wenxiu Liu; Bangwang Li; Junfa Zhu; Yang Pan; et al. (Science Bulletin, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

Fracture evolution and differential mechanical response of surrounding rock in deep tunnel excavation: A case study under complex geological conditions - Xiaojun Yu; Xizhi Zhang; Xia-Ting Feng; Feiyan Wang; Ming Shi; Chengxiang Yang; Huanzhen Luo; Yaping Yang; Yushan Wang (Engineering Geology, 2026)

Confined antisolvent precipitation enables efficient drug encapsulation in microgels for effective gouty arthritis therapy - Lumin Yang; Jinhui Lin; Shuxian Wang; Zhenyang Wei; Xiaolong Zhan; Mingyu Zhu; Yaping Ding; Wei Li (Chemical Engineering Journal, 2026)

Production of neofemales by 17β-estradiol and YY super-male breeding in northern snakehead (Channa argus) - Mi Ou; Yang Zhang; Rong Huang; Yaping Wang; Jianxiong Yin; Qing Luo; Kunci Chen; Haiyang Liu; Xincheng Zhang; Shuzhan Fei; Yuandong Sun; Baixiang Chen; et al. (Aquaculture, 2026)

Resveratrol can inhibit porcine reproductive and respiratory syndrome virus infection in vitro and in vivo by inhibiting PI3K/Akt signaling pathway - Yaping Chen; Wenshuang Chen; Xinqi Song; Xinyi Zhao; Li Yang; Ruoyu Zhao; Meilong Song; Bingbing Zhang; Dongbo Sun (Veterinary Microbiology, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

A quantitative assessment framework for ship collision risk: Integrating spatiotemporal urgency analysis - Yu Chen Xin; Xiong Guan Bao; Yaping Yang (Ocean Engineering, 2026)

Orchestrating ion conduction and interface stability with a montmorillonite filler for dendrite-free and shuttle-free quasi-solid zinc-iodine batteries - Yaping Wang; Xingyun Yang; Miaomiao Zhao; Wenyan Wang; Bin Guo; Yifang Zhang (Chemical Engineering Journal, 2026)

Effects of roads on animals and mitigation measures in Asia - Haotong Su; Yun Wang; Qilin Li; Yangang Yang; Abudusaimaiti Maierdiyali; Shuangcheng Tao; Yaping Kong; Jiding Chen; Jiapeng Qu; Yongshun Han; Aili Kang; Shu Chen; et al. (Biological Conservation, 2026)

Local actors and urban green development in China's energy-rich regions: a case study of the Shanxi-Shaanxi-Inner Mongolia region - Binkai Zheng; Yongyong Song; Yaping Wang; Siyou Xia; Xiping Yang; Beibei Ma; Dongqian Xue (Applied Geography, 2026)

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Interface layer-assisted construction of metal organic framework based porous liquids for high performance CO2 selective separation - Zheng Dong; Yangyang Xin; Bowen Xiang; Ruilu Yang; Menglin Zhu; Baolu Cui; Chenjiao Xie; Shuangshuang Long; Wenwu Zhou; Jianwei Liu; Libing Qian; Hongze Guo; et al. (Journal of Environmental Chemical Engineering, 2025)

Highly efficient biophotoelectrochemical methanogenesis coupling with water sterilization via robust interfacial electronic communication - Jing Hu; Chaohui Yang; Yaping Qi; Mingqiu Hong; Jiajing Chen; Guoping Ren; Jie Ye (Chemical Engineering Journal, 2025)

Unveiling the stepwise catalysis of Ni Fe bimetallic single-atom sites toward high-efficiency lithium–sulfur batteries - Yaping Yan; Yi Yang; Zhihui Zhang; Changzheng Xin; Nan Yang; Tianwei He; Shude Liu; Zixu Sun; Yusuke Yamauchi; Ling Kang (Chemical Engineering Journal, 2025)

Exploring the potential of UAV-based thermal imagery for monitoring diurnal variations in the microscale urban thermal environment - Meng Ji; Yongming Xu; Shanyou Zhu; Yang Zhang; Yan Xin; Yaping Mo (Energy and Buildings, 2025)

The dual-function of VN catalytic sites at cathode and anode toward high-performance lithium‑sulfur batteries - Yaping Yan; Yi Yang; Liu Yang; Xuefeng Luo; Guangzhao Wang; Qingquan Xue; Andreu Cabot; Hua Kun Liu; Shi Xue Dou; Zixu Sun (Chemical Engineering Journal, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

Transcriptional repression of CYP26B1 by EBF2 activates retinol metabolic pathway: A strategy to enhance lipid storage and marbling potential of beef - Yaping Song; Chenglei Song; Jiupan Zhang; Dongmei Yang; Chao Jiang; Ruopu Jiao; Hongfang Gong; Yilun Ma; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Yun Ma; Guijie Zhang; et al. (Food Bioscience, 2025)

Alamandine inhibits pathological retinal neovascularization by targeting the MrgD-mediated HIF-1α/VEGF pathway - Kun Zhao; Yaping Jiang; Wen Huang; Yukang Mao; Yihui Chen; Peng Li; Chuanxi Yang (Journal of Zhejiang University-SCIENCE B, 2025)

Assessment for the wildlife crossing structures along the Qinghai-Tibet railway - Abudusaimaiti Maierdiyali; Yun Wang; Jiding Chen; Runsheng Li; Mei Luo; Xueyang Li; Yangang Yang; Shuangcheng Tao; Yaping Kong; Hao Wang; Zhi Lu (Transportation Research Part D: Transport and Environment, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Unraveling the chrono-regulatory function of PhoP in nitrogen metabolism: A multi-scale engineering framework aimed at optimizing the synthesis of poly-γ-glutamic acid in Bacillus licheniformis - Qing Zhang; Shisi He; Zhihao Zhu; Fangzhou Cheng; Yaping Jin; Wanying Zhu; Fan Yang; Yaozhong Chen; Mengyuan Zhang; Xin Li; Dongbo Cai; Shouwen Chen (Chemical Engineering Journal, 2025)

The interspecies relationships among the wildlife crossing structures of the Qinghai-Tibet Railway - Abudusaimaiti Maierdiyali; Yun Wang; Jiding Chen; Runsheng Li; Yangang Yang; Shuangcheng Tao; Yaping Kong; Zhi Lu (Journal for Nature Conservation, 2025)

Assembly of T4 bacteriophages with β-galactosidase for electrochemical detection of Escherichia coli K12 - Qiaoli Yang; Yaping Wang (Food Chemistry, 2025)

Yield variation in early-maturing cotton in response to sowing dates and growing seasons is associated with differential resource utilization - Yadi Mi; Yaru Wang; Fengqi Wu; Yingchun Han; Beifang Yang; Yaping Lei; Shiwu Xiong; Xiaoyu Zhi; Yabing Li (European Journal of Agronomy, 2025)

Introducing transition metal cations to promote the oxygen reduction kinetics of double perovskite as SOFC cathode - Jie Yang; Yaping Zhang; Xiaofei Zhu; Jinghe Bai; Shangyu Li; Wenfu Yan; Defeng Zhou (Chemical Engineering Journal, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

Progress on the mechanism of natural polysaccharides in the treatment of arthritis - Lili Yuan; Michael Adu-Frimpong; Hong Chen; Yaping Yang; Jiangnan Yu; Huiya Wang; Yuxiang He; Elmurat Toreniyazov; Xia Cao; Qilong Wang; Ximing Xu (Inflammopharmacology, 2025)

Self-adapting deflection contact effect for rock fracture deformation - Haichun Ma; Yanan Wang; Yang Xu; Jiazhong Qian; Yaping Deng (Acta Geophysica, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

From victims to protectors: Microalgae's unexpected capacity for diuron elimination - Zhangzhang Xie; Cuiyun Yang; Ju Zhang; Yaping Zhang; Oumei Wang; Ying Wang; Fanghua Liu (Journal of Hazardous Materials, 2025)

Zwitterionic-based hybrid monoliths for capillary microextraction of polypeptides in dairy products - Xiaoyun Lei; Yaping Jiang; Yang Li; Yanping Duan; Ting Guo; Tianlei Zhang; Zuoping Zhao; Huiping Dai; Xiaohui Ji (Food Chemistry, 2025)

Synthesis of a novel tricarboxylic acid monomer and construction of branched polybenzimidazole membranes for vanadium redox flow battery - Huiting Li; Jun Long; Wenheng Huang; Xiyang Liu; Jinchao Li; Liang Chen; Qin Chen; Qianqian Liang; Zhengjin Yang; Yaping Zhang (Chemical Engineering Journal, 2025)

Quantitative climate reconstruction of the Mid- to late Holocene based on pollen records from Northern Shandong, China - Yaping Li; Wenhao Zheng; Wenfei Liu; Kai Su; Wei Liu; Junna Zhang; Kai Ning; Zhenjing Yang; Guiyun Jin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Temporal and spatial changes of ungulate activity before and after the construction of the Qinghai-Tibet railway in Hoh Xil, China - Abudusaimaiti Maierdiyali; Yun Wang; Yangang Yang; Shuangcheng Tao; Yaping Kong; Jiding Chen; Xin Yang; Basanglamao; Hao Wang; Zhi Lu (Journal of Transport Geography, 2025)

Ghβ-LCY1 influences metabolism and photosynthetic in Gossypium hirsutum - Yanmin Qian; Yaping Wang; Yu Zhang; Zongyan Chu; Mengxin Shen; Cheng Zhang; Lihua Huang; Zhihua Yang; Kaiwen Ren; Yuanyuan Shi; Tingting Jiao; Baoting Yang; et al. (Plant Science, 2025)

Impact of Drought on Farmers’ Livelihood Vulnerability: A Case Study of County-level Units in Western Jilin Province, China - Jiani Zhang; Yang Han; Yangang Fang; Yaping Xu; Chunlin Chen; Zhuxin Liu; Feiyu Wang; Lijuan Zhuang; Fang Huang (Chinese Geographical Science, 2025)

Recent advances in fucoidan-based improved delivery systems: Structure, carrier types and biomedical applications - Haifu Jia; Yuanyuan Li; Yaping Zheng; Huabing Wang; Feng Zhao; Xinyan Yang; Qianyu Zhao; Yujun Jiang; Chaoxin Man (Carbohydrate Polymers, 2025)

Tankyrase inhibitor IWR-1 modulates HIPPO and Transforming Growth Factor β signaling in primed bovine embryonic stem cells cultured on mouse embryonic fibroblasts - Yao Xiao; Yujie Wang; Minghao Zhang; Yan Zhang; Zhihua Ju; Jinpeng Wang; Yaran Zhang; Chunhong Yang; Xiuge Wang; Qiang Jiang; Yaping Gao; Xiaochao Wei; et al. (Theriogenology, 2025)

Online SFE-SFC-MS/MS analysis of pyraclostrobin and chiral mefentrifluconazole residues in mango and mango juice - Hao Yang; Yue Geng; Shu Lin; Lu Wang; Yi Peng; Yaping Xu; Wei Jing; Jing Wei; Zeying He; Xiaowei Liu (Food Chemistry, 2025)

The 2-aminoadipic acid (2-AAA) regulates grass carp ULK2 to inhibit GCRV replication - Xinyu Liang; Xuyang Wang; Xiaowen Zou; Qian Wang; Hanyue Wang; Cheng Yang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Libo He (Fish & Shellfish Immunology, 2025)

Microplastics and Dechlorane Plus co-exposure amplifies their impacts on soybean plant - Yu Xie; Junzhe Zhang; Yaping Lyu; Yaqi Jiang; Yi Sun; Ziqi Zhang; Haojie Wei; Xingxin Liu; Yukui Rui; Wenlong Yang; Peng Zhang (Environmental Pollution, 2025)

Boosting electrocatalytic performance of BaPrO3-δ −based cathode catalysts by Co and Ni co-doping for protonic ceramic fuel cells - Bo Liu; Yanping Zheng; Xinwei Yang; Yaping Liu; Dong Yan; Jian Li; Lichao Jia (Chemical Engineering Journal, 2025)

Associations Between Organophosphate Esters Exposure and Metabolic Syndrome: Exploring the Mediating Role of Oxidative Stress and Inflammation in Adults - Sijie Yang; Yaping Li; Ling Liu; Zhengce Wan; Qitong Xu; Chang Xie; Lulu Song; Youjie Wang; Hui Chen; Surong Mei (Exposure and Health, 2025)

Targeting gut-liver axis by dietary lignans ameliorate obesity: evidences and mechanisms - Zhongxing Chu; Zuomin Hu; Yi Luo; Yaping Zhou; Feiyan Yang; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Silver nanoparticle-functionalized covalent organic frameworks for the inhibition of foodborne pathogenic bacteria and their application in green grape preservation - Jiayi Zhou; Sai Zhang; Yu Zhang; Tianliang Liu; Shuying Yang; Gaopeng Lv; Yaping Wang; Kewei Feng; Yahong Yuan; Tianli Yue; Qinglin Sheng (Food Chemistry, 2025)

Rice rhizosphere microbiome is more diverse but less variable along environmental gradients compared to bulk soil - Yaping Guo; Yakov Kuzyakov; Na Li; Bin Song; Zihao Liu; Jonathan M. Adams; Lin Yang (Plant and Soil, 2025)

Peanut–cotton intercropping to enhance soil ecosystem multifunctionality: Roles of microbial keystone taxa, assembly processes, and C-cycling profiles - Shijie Zhang; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Shiwu Xiong; Beifang Yang; Xiaoyu Zhi; Minghua Xin; Yahui Jiao; Xiao-Fei Li; Yabing Li; et al. (Agriculture, Ecosystems & Environment, 2025)

Effect of long-term temperature-controlled rearing on growth traits and sexual maturity of common carp (Cyprinus carpio) - Yongming Li; Kuangxin Chen; Bin Gui; Cheng Yang; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Sinensetin from citrus peel alleviates DSS-induced inflammation by regulating gut microbiota and serum metabolism in mice - Zuomin Hu; Zhongxing Chu; Xuke Ling; Yuchi Wu; Dandan Qin; Feiyan Yang; Xudong Yu; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

The association of organochlorine pesticides and polychlorinated biphenyls exposure with dyslipidemia and blood lipids: The mediating effect of white blood cell counts - Mingye Zhang; Lipan Wang; Xiang Li; Limei Wang; Yaping Li; Sijie Yang; Lulu Song; Zhengce Wan; Yongman Lv; Youjie Wang; Surong Mei (Environmental Pollution, 2024)

Association Between Neuroinflammation and Parkinson’s Disease: A Comprehensive Mendelian Randomization Study - YiNi Wang; XinYu Shi; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Bai-Xiang Li; Kun Ma (Molecular Neurobiology, 2024)

Biochanin A Attenuates Psoriasiform Inflammation by Regulating Nrf2/HO-1 Pathway Activation and Attenuating Inflammatory Signalling - Yaping Lv; Yingsheng Xu; Songchun Liu; Xianjing Zeng; Bin Yang (Cell Biochemistry and Biophysics, 2024)

Unraveling immobilization mechanisms of Cd in soil by MgO-modified palygorskite/biochar composite: DFT calculation and combined-artificial aging - Kunpeng Yang; Bingyue Guo; Kai Shen; Wenxuan Luo; Bin Zhang; Yuxuan Hua; Yaping Zhang (Journal of Environmental Management, 2024)

ZnO nanoparticles induce melanoma-like lesions via recruiting dermal dendritic cells in barrier-damaged skin in mice - Menghan You; Yingying Huang; Yeda Chen; Dan Li; Yaping Tang; Yi kuan Du; Hong Yang; Anfa Liang; Guodong Hu; Yinghua Chen (Food and Chemical Toxicology, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

The nature of synergy effects between VO and TiO2 in low temperature NH3-SCR reaction - Yingying Jin; Jiaying Li; Kaihao Fan; Yong Chen; Yaping Yang; Xuesong Liu (Journal of Environmental Chemical Engineering, 2024)

Amino/MnO2 combined modified biochar for enhancing Pb2+ and Cd2+ removal and mechanisms from aqueous solution - Kunpeng Yang; Kai Shen; Bin Zhang; Yuxuan Hua; Bingyue Guo; Yaping Zhang (Journal of Environmental Chemical Engineering, 2024)

Widely metabolomic combined with transcriptome analysis to build a bioactive compound regulatory network for the fruit growth cycle in Pseudocydonia sinensis - Shuangyu Zhang; Yang Wu; Yanshen Ren; Yaping Xu; Hong An; Qianyi Zhao; Yu Wang; Houhua Li (Food Chemistry, 2024)

Angelica sinensis polysaccharides promote extramedullary stress erythropoiesis via ameliorating splenic glycolysis and EPO/STAT5 signaling-regulated macrophages - Nianci Sun; Ziling Wang; Honghui Jiang; Biyao Wang; Kunhang Du; Caihong Huang; Cheng Wang; Ting Yang; Yaping Wang; Yafei Liu; Lu Wang (Journal of Molecular Histology, 2024)

Regulation of nitrogen metabolism by COE2 under low sulfur stress in Arabidopsis - Vincent Ninkuu; Yaping Zhou; Hao Liu; Susu Sun; Zhixin Liu; Yumeng Liu; Jincheng Yang; Mengke Hu; Liping Guan; Xuwu Sun (Plant Science, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

Analysis of the Relationship Between Parkinson’s Disease and Diabetic Retinopathy Based on Bioinformatics Methods - XinYu Shi; YiNi Wang; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Kun Ma; Bai-Xiang Li (Molecular Neurobiology, 2024)

Individual and joint effects of organophosphate esters and hypertension or diabetes on renal injury among Chinese adults - Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Chang Xie; Zhengce Wan; Lulu Song; Yongman Lv; Youjie Wang; Hui Chen; Surong Mei (International Journal of Hygiene and Environmental Health, 2024)

Network pharmacology combined with molecular docking and molecular dynamic simulation to reveal the potential mechanism of lentinan ameliorating hyperlipidemia - Zhongxing Chu; Linna Zeng; Feiyan Yang; Zuomin Hu; Yi Luo; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Well-cushioned and highly-elastic aerogel for multifunctional intelligent transportation packaging - Ruiming Liu; Xiaosen Pan; Zijun Mao; Zijun Xu; Yaping Zhu; Pan Xue; Zhengjian Zhang; Hongbin Liu; Yang Liu; Bowen Cheng (Chemical Engineering Journal, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Association between organophosphate esters individual and mixed exposure with the risk of hyperlipidemia and serum lipid levels among adults in Wuhan, China - Qitong Xu; Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Zhengce Wan; Lulu Song; Yongman Lv; Hui Chen; Youjie Wang; Surong Mei (Environmental Science and Pollution Research, 2024)

Molecular Cloning and Characterization of Scavenger Receptor Class B Type 1 in Grass Carp (Ctenopharyngodon idellus) and Its Expression Profile following Grass Carp Reovirus Challenge - Yang Zhang; Jiayuan Shi; Yuntao Lu; Qing Luo; Pengfei Chu; Rong Huang; Kunci Chen; Jian Zhao; Yaping Wang; Mi Ou (Fishes, 2024)
As a member of the pattern recognition receptor (PRR) class, scavenger receptor class B type 1 (SRB1) plays a key role in innate immunity. Grass carp (Ctenopharyngodon idellus) ranks among the most extensively cultivated freshwater aquaculture species in China. However, little is known about the function of SRB1 in C. idellus. In this research study, a SRB1 gene was identified in C. idellus, named CiSRB1. The full-length cDNA of CiSRB1 is 2486 bp long, with an open reading frame (ORF) of 2486 bp encoding a 497 amino acid (aa) protein containing a conserved CD36 domain. The identified genomic DNA length of CiSRB1 is 20,042 bp, including 12 exons and 11 introns. The predictive analysis of protein interactions revealed that CiSRB1 could interact with the outer capsid proteins of typical GCRV strains. The tissue distribution of CiSRB1 exhibited age-dependent characteristics. CiSRB1 displayed the highest expression in the intestines and moderate levels in muscle, spleen, liver, and brain of one-year-old grass carp while maintaining relatively low levels in three-year-old grass carp. Following grass carp reovirus (GCRV) infection, notable upregulation of CiSRB1 transcripts was observed in major immune tissues (gills, intestines, spleen, and liver). Furthermore, significant differences were found between one-year-old and three-year-old grass carp, with lower CiSRB1 expression levels being detected in the older group. Additionally, a distinct response to GCRV infection was observed in one-year-old and three-year-old grass carp. It was found that one-year-old individuals had a mortality rate of up to 84% 6 days post-infection (dpi), whereas all three-year-old counterparts survived after GCRV infection. The analysis of GCRV copy numbers across tissues revealed substantially higher levels in one-year-old grass carp compared with their older counterparts, confirming the existence of age-dependent susceptibility to GCRV infection in grass carp. Combined with these results, it was speculated that the decline in cell-surface CiSRB1 expression with age may impede reovirus binding to host cells, potentially explaining why older grass carp demonstrated enhanced resistance to GCRV infection. This observation accentuates the importance of CiSRB1 in the context of GCRV infection and provides insights into age-dependent susceptibility to reovirus.

Associations of exposure to organochlorine pesticides and polychlorinated biphenyls with chronic kidney disease among adults: the modifying effects of lifestyle - Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Zhengce Wan; Lulu Song; Yongman Lv; Dan Luo; Qiang Li; Youjie Wang; Hui Chen; et al. (Environmental Science and Pollution Research, 2024)

Recalcitrant components accumulation in dissolved organic matter decreases microbial metabolic quotient of red soil under long-term manuring - Xiao Yang; Shuai Zhang; Dong Wu; Yaping Huang; Lu Zhang; Kailou Liu; Huiqiao Wu; Shengli Guo; Wenju Zhang (Science of The Total Environment, 2024)

Molecular and radiocarbon constraints on the fate of sedimentary organic carbon in a human-impacted river-dominated ocean margin - Chenglong Wang; Chuchu Zhang; Zhuoyue Zhang; Qihang Liao; Yang Zhang; Ning Wang; Yaping Wang; Xinqing Zou (Marine Geology, 2024)

Methanogen–methanotroph community has a more consistent and integrated structure in rice rhizosphere than in bulk soil and rhizoplane - Wenqi Wang; Yaping Guo; Lin Yang; Jonathan Miles Adams (Molecular Ecology, 2024)
Methanogenic and methanotrophic microbes together determine the net methane flux from rice fields. Despite much research on them as separate communities, there has been little study of combined community patterns, and how these vary between the rhizoplane (root surface), rhizosphere (soil surrounding the root) and bulk soil around rice plants, especially at larger spatial scale. We collected samples from 32 geographically scattered rice fields in east central China, amplicon targeting the mcrA gene for methanogenesis and pmoA gene for methanotrophy by using high‐throughput sequencing. Distinct communities of both methanogens and methanotrophs occurred in each of the three compartments, and predominantly positive links were found between methanogens and methanotrophs in all compartments indicating cross‐feeding or consortia relationships. Methanogens were acting as the network hub in the bulk soil, and methanotrophs in rhizoplane. Network complexity and stability was greater in the rhizosphere than rhizoplane and bulk soil, with no network hubs detected, suggesting the strongest effect of homeostatic influence by plant occurred in the rhizosphere. The proportion of determinism (homogeneous selection) and distance–decay relation (DDR) in rhizoplane was consistently lower than that in the rhizosphere for both communities, indicating weaker phylogenetic clustering in rice root surface. Our results have provided a better understanding of CH 4 oxidation and emission in rice paddy fields and future agriculture management could take into consideration of the subtle variation among different soil compartments and interactions within methanogenic and methanotrophic communities.

Sediment resuspension and transport in the offshore subaqueous Yangtze Delta during winter storms - Min Tian; Haifei Yang; Wenxiang Zhang; Kehui Xu; Benwei Shi; Yaping Wang; Shilun Yang (Frontiers in Marine Science, 2024)
Storm-induced episodic sediment redistribution in coastal systems can reshape geomorphic bodies, disrupt ecosystems, and cause economic damage. However, cold-wave-storm-induced hydrodynamic changes and residual sediment transport in large, exposed subaqueous deltas, such as the Yangtze Delta, are poorly understood because it is typically expensive and difficult to obtain systematic field data in open coast settings during storm events. We conducted a successful field survey of waves, currents, changes in water depth, and turbidity at a station (time-averaged water depth of 20 m) in the offshore subaqueous Yangtze Delta over 10 days during winter, covering two storms and two fair-weather periods. During the storm events, strong northerly winds drove southward longshore currents (~0.2 m/s) and resulted in increased wave height and sediment resuspension, thereby leading to massive southward sediment transport. In contrast, both southward and northward transports were limited during the fair-weather periods. A better understanding of the storm-induced sediment transport can be obtained by using an approximately half-day lag in sediment transport behind wind force, given the time needed to form waves and longshore drift, the inertia of water motion, and the slow settling velocity of fine-grained sediment. Our results directly support previous findings of southward sediment transport from the Yangtze Delta during winter, which is deposited in the Zhejiang–Fujian mud belt in the inner shelf of the East China Sea. In addition, the southward sediment transport from the Yangtze Delta occurs mainly during episodic storm events, rather than during the winter monsoon, and winter storms dominate over typhoons in driving southward sediment transport from the delta. This study highlights the importance of storms, especially during winter storms, in coastal sediment redistribution, which is of particular significance when considering the projected increase in storm intensity with global warming.

Functional comparison of Rab3aa and Rab3ab in grass carp (Ctenopharyngodon idella) immune response and GCRV replication - Lifei Luo; Lv Xiong; Cheng Yang; Libo He; Lanjie Liao; Yongming Li; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Evaluation of the effect of road barriers on wildlife habitats - Yangang Yang; Yun Wang; Hongping Zhou; Xueping Chen; Shuangcheng Tao; Yaping Kong (Transportation Research Part D: Transport and Environment, 2024)

Effects of pyrite, quartz and sodium sulfite on roasting of a refractory sulfide concentrate and gold, silver, copper leaching during cyanidation - Wei Yang; Qian Wang; Yaping Wang; Tao Long; Sha Deng (Hydrometallurgy, 2024)

Biological functions of active ingredients in quinoa bran: Advance and prospective - Feiyan Yang; Tianyi Guo; Yaping Zhou; Shuai Han; Shuguo Sun; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2024)

Super absorbent resilience antibacterial aerogel with curcumin for fresh pork preservation - Fangqu Wang; Zipeng Xu; Lin Chen; Ziyan Qiao; Yayun Hu; Xiaojing Fan; Yaping Liu; Zhuangli Kang; Feng Huang; Minyi Han; Huijuan Yang; Xianchao Feng (Food Control, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

An Advanced Molecularly Imprinted Photochemical Sensor Based Carbon Quantum dots for Highly Sensitive Detection of Chloramphenicol in Food - Hao Liu; Jing Yang; Xuyuan Sun; Peijie Wu; Guan Wang; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Progress in understanding resistant-starch formation in hydroxypropyl starch: A minireview - Hongxin Jiang; Yaping Feng; Jay-lin Jane; Yunfei Yang (Food Hydrocolloids, 2024)

Chemically tailored molecular surface modification of bamboo pulp fibers for manipulating the electret performance of electret filter media - Chunxia Pang; Huanhuan You; Sijie Lei; Fan Su; Lili Liang; Zhanguo Li; Xiaoyan Lin; Yaping Zhang; Hao Zhang; Xunhai Pan; Yang Hu (Carbohydrate Polymers, 2024)

Grass carp peroxiredoxin 5 and 6-mediated autophagy inhibit grass carp reovirus replication and mitigate oxidative stress - Qian Wang; Xinyu Liang; Hanyue Wang; Cheng Yang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Libo He (Fish & Shellfish Immunology, 2024)

Cracking formation and evolution in surrounding rock of a deep fractured rock mass roadway: A study of the 790-m level segment engineering at the Jinchuan Mine, China - Xiaojun Yu; Yaping Yang; Xifan Li; Huanzhen Luo; Yushan Wang; Xizhi Zhang; Yongyuan Kou; Hongye Li; Yangyi Zhou (Engineering Geology, 2024)

On-site smartphone detection of ethanol content using paper-based colorimetric polydiacetylene sensor arrays - Dong-En Wang; Changhan Yan; Sirui Bai; Yaping Zhang; Wenjing Huo; Kaiting Ning; Lei Zhao; Hui Yang; Huiyun Xu (Chemical Engineering Journal, 2024)

Nanocellulose based ultra-elastic and durable foams for smart packaging applications - Yang Liu; Yaping Zhu; Zijun Xu; Xin Xu; Pan Xue; Hong Jiang; Zhengjian Zhang; Meng Gao; Hongbin Liu; Bowen Cheng (Carbohydrate Polymers, 2024)

N-cycle gene abundance determination of N mineralization rate following re-afforestation in the Loess Plateau of China - Yaping Zhao; Yuqing Zhao; Shuohong Zhang; Yulin Xu; Xinhui Han; Gaihe Yang; Chengjie Ren (Soil Ecology Letters, 2024)

Description of Microbacterium dauci sp. nov., a plant growth hormone indoleacetic acid-producing and nitrogen-fixing bacterium isolated from carrot rhizosphere soil - Jiawen Zheng; Yunyu Liao; Yang Li; Dongsheng Li; Yaping Sun; Zijun Xiao (Archives of Microbiology, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Long-term manuring facilitates glomalin-related soil proteins accumulation by chemical composition shifts and macro-aggregation formation - Hongbo Yang; Qiong Xiao; Yaping Huang; Zejiang Cai; Dongchu Li; Lei Wu; Jeroen Meersmans; Gilles Colinet; Wenju Zhang (Soil and Tillage Research, 2024)

Effect of ferric ions on Cronobacter sakazakii growth, biofilm formation, and swarming motility - Yang Wang; Na Ling; Yaping Wang; Dexin Ou; Zhao Liang; Guoqing Li; Hongyuan Zhao; Yingwang Ye (International Journal of Food Microbiology, 2024)

Reproductive hormones, organophosphate esters and semen quality: Exploring associations and mediation effects among men from an infertility clinic - Yaping Li; Zhiyi Zheng; Dan Luo; Chong Liu; Sijie Yang; Yingjun Chen; Qian Hu; Wenqing Lu; Yixin Wang; Surong Mei (Environmental Research, 2024)

Calcium signal regulated carbohydrate metabolism in wheat seedlings under salinity stress - Ya Zhang; Dan Qiao; Zhe Zhang; Yaping Li; Shuqian Shi; Yingli Yang (Physiology and Molecular Biology of Plants, 2024)

Osthole protects H9c2 cardiomyocytes against trastuzumab-induced damage by enhancing autophagy through the p38MAPK/mTOR signaling pathway - Huan Hou; Yaping Yang; Rong Chen; Zhiping Guo (Toxicology in Vitro, 2023)

Purification and characterization of a glycoprotein from Sipunculus nudus and its immune-enhancing activity to RAW 264.7 macrophages - Xuli Lu; Yaping Dai; Shengtao Yang; Tengfei Fu; Yunxia He; Fanke Zeng; Tinghui Chen; Yupo Cao; Ruyi Li; Jihua Li; Wei Zhou (Food Research International, 2023)

The investigation of circRNA profiling reveals the regulatory role of the hsa_circ_0000375/miR-7706 pathway in breast cancer - Haoqi Wang; Fei Liu; Jing Xue; Yaping Liu; Wei Gao; Shan Yang; Yunzhe Mi; Xi Zhang; Shan Gao; Cuizhi Geng (Molecular Biology Reports, 2023)

Comparative analysis of the transcriptional responses of Acetilactobacillus jinshanensis BJ01 to organic acids - Weifang Liao; Yaping Li; Yuan Zhang; Yibin Yang; Tuanyuan Yang; Lihong Miao (Archives of Microbiology, 2023)

Predictors of unprovoked seizures in intracerebral hemorrhages - Jing Qiang; Yanyan Wang; Qiongqiong Zhai; Jing Zhao; Yaping Yang; Weiping Wang (Acta Neurologica Belgica, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Neoproterozoic subduction-related active rifting in the South China Craton: insights from geochemical and zircon Hf isotopic data - Weizhen Tian; Guanghui Wu; Yaping Wang; Yang Shuai; R. Damian Nance; Xiaojun Zhou; Hakro Ahmed Suhail; Chen Zhang; Bo Zheng (International Geology Review, 2023)

Synergistic catalytic wet oxidation of ammonia over carbon-supported low-loading Ru/Cu bimetallic catalyst - Donglin Yang; Bingxiao Feng; Yaping Liu; Chaoting Deng; Hengjun Gai; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Journal of Environmental Chemical Engineering, 2023)

Effect of pore-throat structure on air-foam flooding performance in a low-permeability reservoir - Guangfeng Liu; Yaping Ding; Juntao Wang; Lizhen Ge; Xiaoming Chen; Daoyong Yang (Fuel, 2023)

Noncovalent co-assembly of aminoglycoside antibiotics@tannic acid nanoparticles for off-the-shelf treatment of pulmonary and cutaneous infections - Guang Yang; Changrong Wang; Yaping Wang; Xiaoqing Liu; Ye Zhang; Ming Xu; Hongzhang Deng; Weiwei Wang (Chemical Engineering Journal, 2023)

Establishment of a halotolerant bioremediation platform from Halomonas cupida using synthetic biology approaches - Wanwan Zhao; Weini Xiong; Yujie Liu; Hongfu Guo; Siqi Wang; Yaping Chen; Ruihua Liu; Bingzhi Li; Chao Yang (Chemical Engineering Journal, 2023)

The role of HBV cccDNA in occult hepatitis B virus infection - Pei He; Peixin Zhang; Yaping Fang; Ning Han; Wensu Yang; Zhaoxin Xia; Yi Zhu; Zhenhua Zhang; Jilu Shen (Molecular and Cellular Biochemistry, 2023)

Remediation and resource utilization of petroleum-contaminated soil by pyrite-assisted pyrolysis as bifunctional materials to adsorb heavy metal and activate peroxymonosulfate oxidation - Tianci Yang; Yaping Liao; Mingxin Wang; Zhiwei Zheng; Meng Yao (Science of The Total Environment, 2023)

A step closer to real practice: Integrated tandem photocatalysis-biofilm process towards degradation of crude oil - Xin Hu; Yaping Pan; Shanshan Zhao; Feifei Zhang; Fengshu Li; Zhe Li; Haoshuai Li; Yiming Li; Jinren Lu; Xiaolong Yang; Mutai Bao (Journal of Environmental Management, 2023)

Au loaded mesoporous SiO2/gelatin hydrogel: Detecting low humidity and NH3 - Zhiyan Ma; Yunlong Yu; Ke Wu; Yaping Song; Sen Liu; Xi Yang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2023)

Sodium acetate trihydrate/melamine foam composite PCM encapsulated by CuS/rGO modified epoxy resin and endowed with light-to-heat conversion properties - Henghua Zhang; Qianbin Dong; Yaping Tang; Jialing Wu; Wenjian Bi; Yue Gao; Jiabang Wang; Hui Yang (Chemical Engineering Journal, 2023)

Assessing Spatio-Temporal Variability of Soil Phosphorus in Different Cotton-Based Cropping Systems Using Geo-Statistics - Li Teng; Xiong Shiwu; Wang Zhanbao; Li Xiaofei; Han Yingchun; Wang Guoping; Lei Yaping; Feng Lu; Yang Beifang; Zhi Xiaoyu; Fan Zhengyi; Li Yabing (Journal of Soil Science and Plant Nutrition, 2023)

Highly efficient catalytic degradation of dicamba using Fe3O4/montmorillonite composite: Mechanism and toxicity assessment - Yu Ouyang; Guangyong Zeng; Wei Zhu; Xuemei Yao; Mengyun Yang; Xiuyu Long; Jie Zheng; Yaping Tao; Yaocheng Deng; Chunxia Ding (Process Safety and Environmental Protection, 2023)

Optimizing plant type structure to adjust the temporal and spatial distribution of water consumption and promote the growth and yield formation of cotton - Yaru Wang; Jiale Chen; Fengqi Wu; Beifang Yang; Yingchun Han; Lu Feng; Zhanbiao Wang; Xiaofei Li; Yaping Lei; Shiwu Xiong; Guoping Wang; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Influencing mechanism and hydrogeological implications of water level fluctuation of lakes in the northern Qaidam Basin, Qinghai-Tibet Plateau - Yaping Cheng; Qishun Fan; Tianyuan Chen; Haotian Yang; Qingkuan Li; Chunmei Han (Journal of Oceanology and Limnology, 2023)

Dual recognition elements for selective determination of progesterone based on molecularly imprinted electrochemical aptasensor - Yan Huang; Daixin Ye; Jing Yang; Wenyi Zhu; Li Li; Yaping Ding (Analytica Chimica Acta, 2023)

One‐kilometre monthly air temperature and precipitation product over the Mongolian Plateau for 1950–2020 - Ying Xin; Yaping Yang; Xiaona Chen; Xiafang Yue; Yangxiaoyue Liu; Cong Yin (International Journal of Climatology, 2023)
The fragile ecological environment of the Mongolian Plateau (MP) is sensitive to climate change. It is necessary to fully understand the temperature and precipitation changes on the MP to ensure regional sustainable development. Most existing studies are conducted based on station observations which suffer from sparse distribution and limited spatial representativeness and cannot perfectly represent the climatic conditions of the whole region. By contrast, the long‐term, spatially continuous reanalysis products offer new opportunities for MP climate change research. However, the coarse spatial resolution and large uncertainties of reanalysis data limit their applicability to provide reliable climate information at finer scales. Within the delta downscaling framework, we downscale and correct the state‐of‐the‐art European Centre for Medium‐range Weather Forecasts ReAnalysis 5 land portion (ERA5‐Land) using a high‐resolution WorldClim reference climatology and generate a long‐term (1950–2020) 1‐km monthly air temperature and precipitation downscaled dataset. During the downscaling process, the results obtained by nearest neighbour, bilinear and bicubic interpolation methods are evaluated and compared. Air temperature result of bilinear method and precipitation result of nearest neighbour method, which have the best accuracy, are taken as the final downscaled data. The evaluation shows that the downscaled data has acceptable accuracy (overall MBE = −0.41°C, Corr = 0.997, RMSE = 1.51°C for air temperature, and MBE = 1.58 mm·month −1 , Corr = 0.747, RMSE = 24.24 mm·month −1 for precipitation), and outperforms the original ERA5‐Land and widely used Climatic Research Unit (CRU) data. In addition, the downscaled data can also provide accurate and detailed temperature and precipitation change trends over the MP. With fine spatial resolution, long‐time span and good spatial continuity, the downscaled air temperature and precipitation will be a useful data source to explore climate change over the MP.

Design of bifunctional TiO2-SSZ-13 mixed supports for potassium-resistant vanadia catalysts for NH3-SCR - Xuesong Liu; Yaping Yang; Jiaying Li; Yang Gao; Kaihao Fan; Yanghui Wang; Xintao Xu; Letong Yang; Xiaodong Wu (Fuel, 2023)

Synergistic effects of combined treatment of 1,2-dichloroethane and high-dose ethanol on liver damage in mice and the related mechanisms - Jinhan Yang; Lin Zhang; Tong Wang; Jiajia Zhang; Mingyue Li; Xiaoxia Jin; Xiaoqiong Tan; Gaoyang Wang; Fenghong Zhao; Yaping Jin (Food and Chemical Toxicology, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

Lacticaseibacillus casei LH23 Suppressed HPV Gene Expression and Inhibited Cervical Cancer Cells - Shiyue Hu; Yunpeng Hao; Xiao Zhang; Yaping Yang; Meiling Liu; Nan Wang; Tong-Cun Zhang; Hongpeng He (Probiotics and Antimicrobial Proteins, 2023)

The nitrogen footprint and reactive nitrogen reduction potential of cotton production in China - Weibin Huang; Fengqi Wu; Zhenggui Zhang; Yongming Meng; Jian Wang; Qinqin Li; Yingchun Han; Lu Feng; Xiaofei Li; Guoping Wang; Yaping Lei; Zhengyi Fan; et al. (Journal of Cleaner Production, 2023)

The pollution reduction effect of official turnover: evidence from China - Xingwang Zhu; Yaping Yang (Science of The Total Environment, 2023)

Origin, composition, and accumulation of dissolved organic matter in a hypersaline lake of the Qinghai-Tibet Plateau - Yaoling Zhang; Keli Yang; Hongmei Chen; Yaping Dong; Wu Li (Science of The Total Environment, 2023)

Spatial-temporal variability pattern of multi-depth soil moisture jointly driven by climatic and human factors in China - Yangxiaoyue Liu; Yaping Yang (Journal of Hydrology, 2023)

Enhanced performance and DFT study of sulfur poisoning mechanism of modified Al2O3 catalyst in COS hydrolysis - Peng Wu; Shipeng Ding; Kai Shen; Hongqiang Yang; Sheng Wang; Shule Zhang; Yaping Zhang (Fuel, 2023)

Neural Network, Nonlinear-Fitting, Sliding Mode, Event-Triggered Control under Abnormal Input for Port Artificial Intelligence Transportation Robots - Yaping Zhu; Qiang Zhang; Yang Liu; Yancai Hu; Sihang Zhang (Journal of Marine Science and Engineering, 2023)
A new control algorithm was designed to solve the problems of actuator physical failure, remote network attack, and sudden change in trajectory curvature when a port’s artificial intelligence-based transportation robots track transportation in a freight yard. First of all, the nonlinear, redundant, saturated sliding surface was designed based on the redundant information of sliding mode control caused by the finite nature of control performance; the dynamic acceleration characteristic of super-twisted sliding mode reaching law was considered to optimize the control high frequency change caused by trajectory mutation; and an improved super-twist reaching law was designed. Then, a nonlinear factor was designed to construct a nonlinear, fault-tolerant filtering mechanism to compensate for the abnormal part of the unknown input that cannot be executed by adaptive neural network reconstruction. On this basis, the finite-time technology and parameter-event-triggered mechanism were combined to reduce the dependence on communication resources. As a result, the design underwent simulation verification to verify its effectiveness and superiority. In the comparative simulation, under a consistent probability of a network attack, the tracking accuracy of the algorithm proposed in this paper was 22.65%, 12.69% and 11.48% higher those that of the traditional algorithms.

Prenatal BPA exposure disrupts male reproductive functions by interfering with DNA methylation and GDNF expression in the testes of male offspring rats - Yaping Mao; Dan Li; Qiaoqiao Yang; Xiucong Pei; Zhiwen Duan; Mingyue Ma (Environmental Science and Pollution Research, 2023)

Formation of organic chloride in the treatment of textile dyeing sludge by Fenton system - Xiaojun Lai; Xun-an Ning; Yang Li; Nuoyi Huang; Yaping Zhang; Chenghai Yang (Journal of Environmental Sciences, 2023)

Activation of Persulfate Oxidation by Pyrolytic Derivatives from Petroleum Contaminated Soil: Efficiency, Mechanism and Resources Utilization - Mingxin Wang; Tianci Yang; Yaping Liao (Water, Air, & Soil Pollution, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Structural elucidation of a novel polysaccharide from Ophiopogonis Radix and its self-assembly mechanism in aqueous solution - Bei Wang; Bin Huang; Bing Yang; Liang Ye; Jingqi Zeng; Zhiwei Xiong; Yaping Chen; Shuchen Guo; Yanjun Yang; Weikun Ma; Maomao Zhu; Xiaobin Jia; et al. (Food Chemistry, 2023)

Orychophragmus violaceus/cotton relay intercropping with reduced N application maintains or improves crop productivity and soil carbon and nitrogen fractions - Zhenggui Zhang; Jian Wang; Shiwu Xiong; Weibin Huang; Xiaofei Li; Minghua Xin; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Beifang Yang; Yabing Li; et al. (Field Crops Research, 2023)

Investigating aerosol chemistry using Real-Time Single Particle Mass Spectrometry: A viewpoint on its recent development - Xiaofei Wang; Yaping Zhang; Xin Yang (Applied Geochemistry, 2023)

Quantitative evaluation of variation and driving factors of the regional water footprint for cotton production in China - Qinqin Li; Weibin Huang; Jian Wang; Zhenggui Zhang; Yabing Li; Yingchun Han; Lu Feng; Xiaofei Li; Beifang Yang; Guoping Wang; Yaping Lei; Shiwu Xiong; et al. (Sustainable Production and Consumption, 2023)

Expanding the gallery of solvent-free nanofluids: Using layered double hydroxides as core nanostructures - Xiaoqian Ju; Zhiyuan Yang; Dechao Wang; Xinbo Duan; Yangyang Xin; Hanbo Zhu; Xiaoqian Li; Yinyan Li; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2023)

Carbon layer encapsulation strategy for designing multifunctional core-shell nanorod aerogels as high-temperature thermal superinsulators - Fengqi Liu; Chenbo He; Yonggang Jiang; Yaping Yang; Fei Peng; Lanfang Liu; Jing Men; Junzong Feng; Liangjun Li; Guihua Tang; Jian Feng (Chemical Engineering Journal, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Construction of WO3 nanocubes@Loess for rapid photocatalytic degradation of organics in wastewater under sunlight - Hua Yang; Peiyu Cao; Yaping Zhang; Meiling Zhou; Qianqian Wang; Rongmin Wang; Pengfei Song; Yufeng He (Environmental Science and Pollution Research, 2022)

How industrial water resources green efficiency varies in China: a case study of the Yangtze River Economic Belt considering unexpected output - Dalai Ma; Fengtai Zhang; Yaping Xiao; Lei Gao; Hongbo Liao; Na Zhao; Yuedong Xiao; Xingyu Yang; Wenli Wu (Environment, Development and Sustainability, 2022)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Vegetation dynamics and their relationships with climatic factors in the “Golden Triangle” region - Yaping Zhu; Juchao Zhao; Pifeng Lei; Kun Yang; Shaohua Zhang; Xiaoxue Yin; Yan Jiang (Environmental Science and Pollution Research, 2022)

Enhanced Influenza Immunity by Nasal Mucosal Administration of the TPGS-Modified Liposomal Vaccine - Shijie Ma; Rui Yu; Yaping Mai; Na Yu; Ting Gao; Jianhong Yang (AAPS PharmSciTech, 2022)

A FRET Fluorescent Sensor for Ratiometric and Visual Detection of Sulfide Based on Carbon Dots and Silver Nanoclusters - Jing Yang; Yan Huang; Hanyue Cui; Li Li; Yaping Ding (Journal of Fluorescence, 2022)

Carbon footprint analysis of straw collection, transportation, and storage system for power generation in China based on emergy evaluation - Yufeng Sun; Bin Yang; Yapeng Wang; Zipeng Zheng; Jinwei Wang; Yaping Yue; Wenlong Mu (Environmental Science and Pollution Research, 2022)

Biparental genetic mapping reveals that CmCLAVATA3 (CmCLV3) is responsible for the variation in carpel number in melon (Cucumis melo L.) - Lihuan Wang; Yaping Wang; Feishi Luan; Xian Zhang; Jingchao Zhao; Zhongzhou Yang; Shi Liu (Theoretical and Applied Genetics, 2022)

Regulation of wound healing and fibrosis by galectins - Dong Yu; Ming Bu; Ping Yu; Yaping Li; Yang Chong (Journal of Molecular Medicine, 2022)

PLC1 and H2O2 Mediated the Allelopathic Effect of Oridonin on Root Growth in Arabidopsis thaliana - Yue Zhang; Yanhuang An; Ning Yang; Wei Wang; Ruirui Liu; Run Gao; Yaping Zhou (Journal of Plant Growth Regulation, 2022)

A Significant Fluorescent Aptamer Sensor Based on Carbon Dots and Graphene Oxide for Highly Selective Detection of Progesterone - Hanyue Cui; Huan Lu; Jing Yang; Yao Fu; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2022)

Soil phosphorus availability and stoichiometry determine microbial activity and functional diversity of fluvo-aquic soils under long-term fertilization regimes - Wei He; Wenhua Ye; Mingjie Sun; Yaping Li; Manman Chen; Meng Wei; Guoqing Hu; Quangang Yang; Hong Pan; Yanhong Lou; Hui Wang; Yuping Zhuge (Journal of Soils and Sediments, 2022)

Changes in Transcriptome and Ultrastructure Reveal Salinity Tolerance of Obscure Puffer Takifugu obscurus - Jun Wang; Xuexia Zhu; Yunfei Sun; Lei Gu; Yaping Wu; Yafen Chen; Zhou Yang (Frontiers in Marine Science, 2022)
Fish can maintain a stable intracellular concentration of ions in environments of variable salinities through osmoregulation. In this study, we focused on obscure puffer Takifugu obscurus ( T. obscurus ), an anadromous fish with high commercial value and rapid depression of wide populations, to investigate changes at molecular and physiological levels underlying salinity tolerance through multifaceted analyses integrating transcriptomics and micrography. We found that with the increase of salinity, the structure of the three main osmoregulation organs, i.e., gill, intestine, and kidney had remarkable changes. The results of transcriptome demonstrated that the ATP-binding box transporter and cyclic adenosine monophosphate (cAMP) signaling pathway in the gill and kidney were significantly reduced. Growth hormone, prolactin, and cortisol regulated more transporters of body composition and stimulated chloride cell proliferation and differentiation, which change the capacity for membrane transport between ion and water molecules. Adenosine-activating protein kinase and thyroid hormone signaling pathway were also significantly upregulated. These transcriptional levels changes of T. obscurus combined with ultrastructure in response to salinity increase indicated that osmoregulation is a complex process involving multiple organs and signaling pathways. Overall, this study can deepen the understanding of osmotic regulation during fish migration.

Metabolite profiling in albino tea mutant Camellia sinensis ‘Fuyun 6’ using LC–ESI–MS/MS - Xinying Lin; Xuejin Chen; Pengjie Wang; Yucheng Zheng; Yongchun Guo; Yaping Hong; Ruxing Yang; Naixing Ye (Trees, 2022)

Correction: Feasibility of nitrate reduction combined with persulfate oxidation in the remediation of groundwater contaminated by gasoline - Huan Wang; Yudao Chen; Lewei He; Yaping Jiang; Yuan Xia; Pengfei Yang (Hydrogeology Journal, 2022)

Feasibility of nitrate reduction combined with persulfate oxidation in the remediation of groundwater contaminated by gasoline - Huan Wang; Yudao Chen; Lewei He; Yaping Jiang; Yuan Xia; Pengfei Yang (Hydrogeology Journal, 2022)

Chemical composition and Pb(II) binding of dissolved organic matter in a hypersaline lake in China - Keli Yang; Yaoling Zhang; Yaping Dong; Wu Li (Journal of Oceanology and Limnology, 2022)

Spring snow depth changes and feedback to surface air temperature across the Tibetan plateau from 1961 to 2013 - Xiaona Chen; Yaping Yang (International Journal of Climatology, 2022)
Spring snow depth (SSD) in the Tibetan Plateau (TP) plays an essential role in snow water estimation, vegetation growth, and climate projections for Southwest China and the surrounding Asian countries. Previous studies have reported a decline in SSD that is associated with increasing surface air temperature ( T s ) across the TP over the past decades. However, only a few studies have explored the potential feedback of SSD to T s , which has hindered the elucidation of the vulnerability of snow cover in the TP against the backdrop of rapid climate change. Based on data from 69 meteorological stations in the central and eastern parts of the TP, this study analyses changes in SSD and its feedback to T s from 1961 to 2013. Overall, a slightly negative trend in SSD was observed from 1961 to 2013, during which two contrasting trends were detected using a piecewise regression approach: an initial increase from 1961 to 1981 (0.12 cm decades −1 , p −1 , p T s anomaly, with sensitivities of −0.050 cm °C −1 ( p −1 ( p T s was attenuated, with averaged feedback values from −1.328°C cm −1 during 1961–2013 to −0.936°C cm −1 during 1982–2013 in latitudes below 3,500 m, distributed in the Qaidam and Yellow River basins, and the upper reaches of the Yangtze River basin. The decrease in feedback from SSD to T s may lead to changes in the mechanism controlling T s dynamics across the TP, which should be considered in climate change projections in future studies.

Longitudinal residual circulation in the South Passage of Yangtze Estuary: Combined influences from runoff, tide and bathymetry - Lifen Zhang; Zuosheng Yang; Fan Zhang; Zhanhai Li; Yaping Wang; Shu Gao (Science China Earth Sciences, 2021)

gga-miR-142-3p negatively regulates Mycoplasma gallisepticum (HS strain)-induced inflammatory cytokine production via the NF-κB and MAPK signaling by targeting TAB2 - Yaping Yang; Yingjie Wang; Mengyun Zou; Ganzhen Deng; Xiuli Peng (Inflammation Research, 2021)

Tracking historical storm records from high-barrier lagoon deposits on the southeastern coast of Hainan Island, China - Liang Zhou; Xiaomei Xu; Yaping Wang; Jianjun Jia; Yang Yang; Gaocong Li; Changliang Tong; Shu Gao (Acta Oceanologica Sinica, 2021)

Pituitary Adenylate Cyclase-Activating Polypeptide Protects Against Cognitive Impairment Caused by Chronic Cerebral Hypoperfusion - Xiaosu Guo; Ye Tian; Yaping Yang; Shiping Li; Li Guo; Jiong Shi (Molecular Neurobiology, 2021)

Nanocrystals for Improving Oral Bioavailability of Drugs: Intestinal Transport Mechanisms and Influencing Factors - Zonghua Tian; Yaping Mai; Tingting Meng; Shijie Ma; Guojing Gou; Jianhong Yang (AAPS PharmSciTech, 2021)

Characterizing temporal behavior of a thermal tracer in porous media by time-lapse electrical resistivity measurements - Ze Yang; Yaping Deng; Jiazhong Qian; Rui Ding; Lei Ma (Hydrogeology Journal, 2021)

Decreased grain size1, a C3HC4-type RING protein, influences grain size in rice (Oryza sativa L.) - Xingjie Zhu; Shengzhong Zhang; Yaping Chen; Changlin Mou; Yunshuai Huang; Xi Liu; Jingli Ji; Jiangfeng Yu; Qixian Hao; Chunyan Yang; Mengying Cai; Thanhliem Nguyen; et al. (Plant Molecular Biology, 2021)

Docetaxel-loaded D-α-tocopheryl polyethylene glycol-1000 succinate liposomes improve lung cancer chemotherapy and reverse multidrug resistance - Na Li; Yaping Mai; Qiang Liu; Guojing Gou; Jianhong Yang (Drug Delivery and Translational Research, 2021)

Two novel compounds from green walnut husks ( Juglans mandshurica Maxim.) - Hong Yang; Chunli Gan; Yaping Guo; Liyuan Qu; Shuang Ma; Yanbin Ren; Xingwen Wang; Libo Wang; Jian Huang; Jinhui Wang (Natural Product Research, 2020)

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Could urinary ACE2 protein level help identify individuals susceptible to SARS-CoV-2 infection and complication? - Xiaotian Ni; Changqing Sun; Yaping Tian; Yanjie Huang; Tongqing Gong; Lan Song; Xing Yang; Kai Li; Nairen Zheng; Jianping Wang; Hongxing Wu; Ruoxian Zhang; et al. (Science China Life Sciences, 2020)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Generation of mice with hepatocyte-specific conditional deletion of sphingosine kinase 1 - Jinfeng Yu; Jiale Dong; Kangdi Chen; Yaping Ding; Zhicheng Yang; Tian Lan (Transgenic Research, 2020)

Interactive effects of exogenous melatonin and Rhizophagus intraradices on saline-alkaline stress tolerance in Leymus chinensis - Yurong Yang; Yaping Cao; Zhenxin Li; Anastasiia Zhukova; Songtao Yang; Jinlong Wang; Zhanhui Tang; Yonghong Cao; Yifei Zhang; Deli Wang (Mycorrhiza, 2020)

Ameliorative effect of naringin against thiram-induced tibial dyschondroplasia in broiler chicken - Xiong Jiang; Aoyun Li; Yaping Wang; Mudassar Iqbal; Muhammad Waqas; Hao Yang; Zhixing Li; Khalid Mehmood; Hammad Qamar; Jiakui Li (Environmental Science and Pollution Research, 2020)

Origin of crystal dolomite and its reservoir formation mechanism in the Xixiangchi Formation, Upper Cambrian in Southeastern Sichuan basin - Xuefei Yang; Zisang Huang; Xingzhi Wang; Yaping Wang; Ke Li; Deming Zeng (Carbonates and Evaporites, 2019)

MiR-19a mediates the negative regulation of the NF-κB pathway in lipopolysaccharide-induced endometritis by targeting TBK1 - Nannan Yin; Yaping Yang; Xiaoyan Wang; Chao Yang; Xiaofei Ma; Aftab Shaukat; Gan Zhao; Ganzhen Deng (Inflammation Research, 2019)

Deep sequencing of small RNAs from 11 tissues of grass carp Ctenopharyngodon idella and discovery of sex‐related microRNAs - Liangming Chen; Rong Huang; Denghui Zhu; Cheng Yang; Libo He; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Journal of Fish Biology, 2019)
This research identified 169 known microRNAs (miRNAs), 380 novel miRNAs, and 30,538 targets in 11 tissues (blood, brain, derma, gill, heart, intestine, kidney, liver, muscle, pronephros, and spleen) from grass carp Ctenopharyngodon idella with high‐throughput sequencing (HTS). Transcripts per million (TPM) expression analysis detected 41 brain‐enriched miRNAs (accounting for 61.19% of all tissue‐enriched miRNAs). Real‐time quantitative PCR (RT‐qPCR) confirmed that 21 of 24 randomly selected tissue‐enriched miRNAs from the TPM analysis were indeed tissue‐enriched ( P dmrt ) involved in sex differentiation. RT‐qPCR revealed that cid‐miR ‐138 was more highly expressed in testis than in ovary ( P dmrt4a ( P cid‐miR ‐138– dmrt4a in neuroendocrine mechanisms related to brain‐pituitary networks during sex development. The discovery of miRNAs from 11 C. idella tissues expands the available fish mi R NA database, and enhances our understanding of the role of sex‐related miRNAs in tissue differentiation and maintenance of specific tissue functions in fishes.

Purification, characterization, and biocatalytic potential of a novel dextranase from Chaetomium globosum - Liu Yang; Nandi Zhou; Yaping Tian (Biotechnology Letters, 2018)

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L. - Lifei Luo; Rong Huang; Aidi Zhang; Cheng Yang; Liangming Chen; Denghui Zhu; Yongming Li; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Functional & Integrative Genomics, 2018)

Stocks and dynamics of particulate and dissolved organic matter in a large, shallow eutrophic lake (Taihu, China) with dense cyanobacterial blooms - Limei Shi; Yaxin Huang; Yaping Lu; Feizhou Chen; Min Zhang; Yang Yu; Fanxiang Kong (Journal of Oceanology and Limnology, 2018)

Chemical characterization of fractions of dissolved humic substances from a marginal sea—a case from the Southern Yellow Sea - Yaoling Zhang; Keli Yang; Jinzhou Du; Fenfen Zhang; Yaping Dong; Wu Li (Journal of Oceanology and Limnology, 2018)

De novo apparent loss-of-function mutations in PRR12 in three patients with intellectual disability and iris abnormalities - Magalie S. Leduc; Marianne Mcguire; Suneeta Madan-Khetarpal; Damara Ortiz; Susan Hayflick; Kory Keller; Christine M. Eng; Yaping Yang; Weimin Bi (Human Genetics, 2018)

Water and CO2 fluxes over semiarid alpine steppe and humid alpine meadow ecosystems on the Tibetan Plateau - Lei Wang; Huizhi Liu; Yaping Shao; Yang Liu; Jihua Sun (Theoretical and Applied Climatology, 2018)

Temporal and spatial variations of aquatic environmental characteristics and sediment bacterial community in five regions of Lake Taihu - Yu Wan; Yang Bai; Jia He; Yaping Zhang; Rongfu Li; Xiaohong Ruan (Aquatic Ecology, 2017)

Erratum to: Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

Dolomitization by penesaline sea water in Early Cambrian Longwangmiao Formation, central Sichuan Basin, China - Xuefei Yang; Hao Tang; Xingzhi Wang; Yaping Wang; Yueming Yang (Journal of Earth Science, 2017)

Classifying the sedimentary environments of the Xincun Lagoon, Hainan Island, by system cluster and principal component analyses - Yang Yang; Shu Gao; Liang Zhou; Yunwei Wang; Gaocong Li; Yaping Wang; Zhuochen Han; Peihong Jia (Acta Oceanologica Sinica, 2017)

Assessing the vulnerability of changing coasts, Hainan Island, China - Yaping Wang; Benwei Shi; Liang Zhang; Jianjun Jia; Xiaomin Xia; Liang Zhou; Rui Yu; Yang Yang; Jianhua Gao (Acta Oceanologica Sinica, 2017)

The response of sedimentary record to catchment changes induced by human activities in the western intertidal flat of Yalu River Estuary, China - Yong Shi; Zhishuai Liu; Jianhua Gao; Yang Yang; Yaping Wang (Acta Oceanologica Sinica, 2017)

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

Optimized expression of prolyl aminopeptidase in Pichia pastoris and its characteristics after glycosylation - Hongyu Yang; Qiang Zhu; Nandi Zhou; Yaping Tian (World Journal of Microbiology and Biotechnology, 2016)

Genome-wide analysis of the terpene synthase gene family in physic nut (Jatropha curcas L.) and functional identification of six terpene synthases - Wangdan Xiong; Pingzhi Wu; Yongxia Jia; Xiaoyi Wei; Liangxiong Xu; Yanfang Yang; Deyou Qiu; Yaping Chen; Meiru Li; Huawu Jiang; Guojiang Wu (Tree Genetics & Genomes, 2016)

Neuroprotective Effect of Osthole on Neuron Synapses in an Alzheimer’s Disease Cell Model via Upregulation of MicroRNA-9 - Shaoheng Li; Yuhui Yan; Yanan Jiao; Zhong Gao; Yang Xia; Liang Kong; Yingjia Yao; Zhenyu Tao; Jie Song; Yaping Yan; Guangxian Zhang; Jingxian Yang (Journal of Molecular Neuroscience, 2016)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The roles of endoplasmic reticulum stress response in female mammalian reproduction - Yanzhou Yang; Xiuying Pei; Yaping Jin; Yanrong Wang; Cheng Zhang (Cell and Tissue Research, 2016)

Kupffer-cell-expressed transmembrane TNF-α is a major contributor to lipopolysaccharide and D-galactosamine-induced liver injury - Peng Yang; Wenjing Zhou; Chenxi Li; Meng Zhang; Yaping Jiang; Rui Jiang; Hongping Ba; Cheng Li; Jing Wang; Bingjiao Yin; Feili Gong; Zhuoya Li (Cell and Tissue Research, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

Trends of subtype variation of human immunodeficiency virus type 1 in Zhejiang Province, China - Yaping Yao; Ruolei Xin; Jiezhe Yang; Yun Xu; Jiafeng Zhang; Yan Xia; Xiaohong Pan; Zhihong Guo; Yanhui Song (Virus Genes, 2015)

Idiomarina atlantica sp. nov., a marine bacterium isolated from the deep sea sediment of the North Atlantic Ocean - Juan Du; Qiliang Lai; Yang Liu; Yaping Du; Xiupian Liu; Fengqin Sun; Zongze Shao (Antonie van Leeuwenhoek, 2015)

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

Removal of trace Cd(II) from water with the manganese oxides/ACF composite electrode - Yaping Chen; Liang Peng; Qingru Zeng; Yang Yang; Ming Lei; Huijuan Song; Liyuan Chai; Jidong Gu (Clean Technologies and Environmental Policy, 2015)

FLT3 and CDK4/6 inhibitors: Signaling mechanisms and tumor burden in subcutaneous and orthotopic mouse models of acute myeloid leukemia - Yaping Zhang; Cheng-Pang Hsu; Jian-Feng Lu; Mita Kuchimanchi; Yu-Nien Sun; Ji Ma; Guifen Xu; Yilong Zhang; Yang Xu; Margaret Weidner; Justin Huard; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Expression and functional analysis of a glycoside hydrolase family 45 endoglucanase from Rhizopus stolonifer - Bin Tang; Yingying Zhang; Yaping Yang; Zhewei Song; Xianglin Li (World Journal of Microbiology and Biotechnology, 2014)

GRP78 expression and regulation in the mouse uterus during embryo implantation - PengFei Lin; YaPing Jin; XiangLi Lan; YanZhou Yang; Fenglei Chen; Nan Wang; Xiao Li; YuJie Sun; AiHua Wang (Journal of Molecular Histology, 2014)

Comparative proteomic and physiological analysis of diurnal changes in Nostoc flagelliforme - Wenyu Liang; Lingxia Wang; Yaping Zhang; Xiaoting Lei; Jia Yang; Xiangrong You; Chi-Lien Cheng; Youwen Zhou; Wei Chen (Journal of Applied Phycology, 2013)

Epimerization of epigallocatechin gallate to gallocatechin gallate and its anti-diabetic activity - Lianwu Xie; Yaping Guo; Bo Cai; Jing Yang (Medicinal Chemistry Research, 2013)

Gender Differences in Preattentive Processing of Facial Expressions: An ERP Study - Qiang Xu; Yaping Yang; Pei Wang; Gang Sun; Lun Zhao (Brain Topography, 2013)

Inhibition of Camellia sinensis (L.) O. Kuntze on Microcystis aeruginosa and isolation of the inhibition factors - Yaping Lu; Jin Wang; Yang Yu; Wen Su; Fanxiang Kong (Biotechnology Letters, 2013)

Analysis of the DNA methylation of maize (Zea mays L.) in response to cold stress based on methylation-sensitive amplified polymorphisms - Xiaohui Shan; Xiaoyu Wang; Guang Yang; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yaping Yuan (Journal of Plant Biology, 2013)

The Effects of Ce on the Proliferation, Osteogenic Differentiation and Mineralization Function of MC3T3-E1 Cells In Vitro - Dandan Liu; Jinchao Zhang; Yaping Li; Shuxiang Wang; MengSu Yang (Biological Trace Element Research, 2012)

Cyanobacteria-blooming water samples from Lake Taihu induce endoplasmic reticulum stress in liver and kidney of mice - Wendi Qin; Liuyan Yang; Xuxiang Zhang; Zongyao Zhang; Lizhi Xu; Jun Wu; Jing An; Yaping Wang (Ecotoxicology, 2012)

The complete mitochondrial genome of the butterfly Apatura metis (Lepidoptera: Nymphalidae) - Min Zhang; Xinping Nie; Tianwen Cao; Juping Wang; Tao Li; Xiaonan Zhang; Yaping Guo; Enbo Ma; Yang Zhong (Molecular Biology Reports, 2012)

Differential gene expression during somatic embryogenesis in the maize (Zea mays L.) inbred line H99 - Lifang Sun; Ying Wu; Shengzhong Su; Hongkui Liu; Guang Yang; Shipeng Li; Xiaohui Shan; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Spontaneous uptake of exogenous DNA by goat spermatozoa and selection of donor bucks for sperm-mediated gene transfer - Yongju Zhao; Mingju Yu; Lingbin Wang; Yaofeng Li; Jingsheng Fan; Qian Yang; Yaping Jin (Molecular Biology Reports, 2012)

Molecular characterization, expression pattern, polymorphism and association analysis of bovine ADAMTSL3 gene - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Yang Jiao; Kui Li (Molecular Biology Reports, 2012)

Identification and characterisation of candidate genes involved in chilling responses in maize (Zea mays L.) - Guang Yang; Hongda Zou; Ying Wu; Hongkui Liu; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Population genetic structure and phylogeographical pattern of rice grasshopper, Oxya hyla intricata, across Southeast Asia - Tao Li; Min Zhang; Yanhua Qu; Zhumei Ren; Jianzhen Zhang; Yaping Guo; K. L. Heong; Bong Villareal; Yang Zhong; Enbo Ma (Genetica, 2011)

Establishment of an aging model of Sca-1+ hematopoietic stem cell and studies on its relative biological mechanisms - Yue Zhou; Bing Yang; Xin Yao; Yaping Wang (In Vitro Cellular & Developmental Biology - Animal, 2011)

Optimization of fermentation conditions for production of xylanase by a newly isolated strain, Penicillium thiersii ZH-19 - Fengjie Cui; Yin Li; Zhiqiang Liu; Hui Zhao; Lifeng Ping; Liying Ping; Yinan Yang; Yaping Xue; Lijiao Yan (World Journal of Microbiology and Biotechnology, 2009)

Effects of in utero meso-2,3-dimercaptosuccinic acid with calcium and ascorbic acid on lead-induced fetal development - Fei Yu; Yingjun Liao; Yaping Jin; Yue Zhao; Yahao Ren; Chunwei Lu; Gexin Li; Yanxi Li; Jun Yang (Archives of Toxicology, 2008)

Therapeutic potentials of combined use of DMSA with calcium and ascorbic acid in the treatment of mild to moderately lead intoxicated mice - Yingjun Liao; Jun Zhang; Yaping Jin; Chunwei Lu; Gexin Li; Fei Yu; Xuping Zhi; Li An; Jun Yang (BioMetals, 2008)

Selection of micronutrients used along with DMSA in the treatment of moderately lead intoxicated mice - Yingjun Liao; Fei Yu; Yaping Jin; Chunwei Lu; Gexin Li; Xuping Zhi; Li An; Jun Yang (Archives of Toxicology, 2008)

Impacts of the large amount of sand mining on riverbed morphology and tidal dynamics in lower reaches and delta of the Dongjiang River - Liangwen Jia; Zhangren Luo; Qingshu Yang; Shuying Ou; Yaping Lei (Journal of Geographical Sciences, 2007)

Genetic Variation and Population Structure of Oriental Migratory Locust, Locusta migratoria manilensis, in China by Allozyme, SSRP-PCR, and AFLP Markers - Xianyun Zheng; Yang Zhong; Yihao Duan; Chunxuan Li; Li Dang; Yaping Guo; Enbo Ma (Biochemical Genetics, 2006)

A Scheme for Scalar Exchange in the Urban Boundary Layer - Yan Yang; Yaping Shao (Boundary-Layer Meteorology, 2006)

Increasing the transient expression of GUS gene in Porphyra yezoensis by 18S rDNA targeted homologous recombination - Hongquan Liu; Wengong Yu; Jixun Dai; Qianhong Gong; Kunfeng Yang; Yaping Zhang (Journal of Applied Phycology, 2003)

Opioid activity of synthetic deltorphin II analogues and their spin labeled derivatives - Dingjian Yang; Rui Wang; Yaping Ma; Yujun Di; Xiaofeng Huo (International Journal of Peptide Research and Therapeutics, 1999)